Pan-Islamisme dan Kebangkitan Islam: Refleksi Filsafat Sosial-Politik Jamaluddin al-Afghani - Andi Saputra (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
This study deals with the al-Afghani’s socio-political thinking, a famous 19th century Muslim leader by carrying out Pan-Islamism as a paradigm of Islamic renewal. Departing from the spirit to free the world of Islam from colonialism and underdevelopment, all forms of imperealism for him are the restraint of human nature, freedom where the spirit of liberation is not only in line with human rights but also in line with the basic teachings of religion (Islam). Therefore, he wanted a form of democratic government as a rejection of an instructive government system (autocracy). Furthermore, Pan-Islamism is not intended to merge Muslim countries under one flag and government, but about how to ground the universal values of Islam in the form of liberation, justice and brotherhood across geographical and ethnic boundaries.___________________Keywords: al-Afghani, Islam, the Unity